An overview of SDN Controllers - Kalaivani, C (International Journal of Computer Sciences and Engineering, 2019)
Software Defined Network is based on separation of network intelligence from packet switching devices and merging network intelligence in a centralized controller. With SDN, Enterprises can manage the entire network from a single SDN controller, irrespective of different vendors of network elements [11].This controller acts as the main brain and act as a strategic control point to decide about routing using OpenFlow protocols. SDN controller is a kind of operating system for network where applications and devices can have communication only through it. In this paper, many SDN controllers are discussed.